2020
DOI: 10.21203/rs.3.rs-34243/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Clinical, Laboratory and Radiological Findings in Iranian Smokers and non- Smokers Patients with COVID-19: A Case Control Study

Abstract: Objective: The current study compared the clinical, laboratory and radiological findings between groups of smokers and non- smokers Iranian patients with COVID-19. Methods: This was a case-control study done on 120 patients with COVID-19 that were admitted to Baqiyatallah hospital, Tehran, Iran during March to May 2020. Our patients were categorized into two groups: smokers (40 patients) and non-smokers (80 age and sex matched controls). Demographic and clinical characteristics, laboratory findings, imaging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…We did not find a study regarding sweating, and to the best of our knowledge, this is the first work to report this. Nikpouraghdam et al 31 suggested an association between weakness and COVID-19 that is the same as our data but is in contrast with the findings of Shi et al 17 Shivering is observed in the cohort of COVID-19, which is reported by Zhu et al 32 too. Fatigue is significantly related with COVID-19 in our cohort which confirms the findings of Qin et al 27 but is in contrast to the findings of Liang et al, 23 Tian et al, 25 Lei et al, 33 and Yan et al 34 A dry cough is reported by Du et al 35 to be related with COVID-19, which is similar with our findings, while such an association is not found by Qin et al, 27 Lei et al, 33 and Shi et al 17 Anorexia is found to be a significant symptom for COVID-19 in our study.…”
Section: Discussionsupporting
confidence: 83%
“…We did not find a study regarding sweating, and to the best of our knowledge, this is the first work to report this. Nikpouraghdam et al 31 suggested an association between weakness and COVID-19 that is the same as our data but is in contrast with the findings of Shi et al 17 Shivering is observed in the cohort of COVID-19, which is reported by Zhu et al 32 too. Fatigue is significantly related with COVID-19 in our cohort which confirms the findings of Qin et al 27 but is in contrast to the findings of Liang et al, 23 Tian et al, 25 Lei et al, 33 and Yan et al 34 A dry cough is reported by Du et al 35 to be related with COVID-19, which is similar with our findings, while such an association is not found by Qin et al, 27 Lei et al, 33 and Shi et al 17 Anorexia is found to be a significant symptom for COVID-19 in our study.…”
Section: Discussionsupporting
confidence: 83%
“…We did not find study regarding sweating, and to best of our knowledge, this is the first work to report this. Nikpouraghdam et al [29] suggested an association between weakness and COVID-19 that is the same with our data but is in contrast with the findings of Shi et al [17]. Shivering is observed in the cohort of COVID-19, which is reported by Zhu et al [30] too.…”
Section: Discussionsupporting
confidence: 81%
“…Radiological imaging techniques, such as computed tomography (CT) scans, have been instrumental in identifying and monitoring the evolution of COVID-19-related lung damage [ 2 ]. Radiological differences between smokers and non-smokers with COVID-19-related lung damage have been the subject of recent research [ 8 , 9 ]. This is because smoking can cause a loss of lung elastic recoil pressure, leading to reduced lung function and increased amenability to respiratory infections, including COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the study observed a slightly lower mortality rate among smokers compared to non-smokers. Overall, the study sheds light on the impact of smoking on clinical outcomes in COVID-19 patients, but further research is needed to fully understand the relationship between smoking and COVID-19 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%